A Study of the Ethnic Tolerance Level among the Students of PFUR in 2008—2011 - Zh V Puzanova; I I Demidova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2012)
The article describes the studies of the level of ethnic tolerance among the students of PFUR. There is a brief description of the applied research instruments on the basis of Bogardus’ scale and the index of national distance status. The authors also analyze the data according to the level of ethnic tolerance to various ethnic groups and the changes in the students’ tolerance levels in the past four years.